Effect of phosphorus application on economic yield, quality and phosphorus utilisation efficiency of purple-fleshed sweetpotato - Ming Liu; Wenjing Fan; Rong Jin; Peng Zhao; Qiangqiang Zhang; Xiaoya Zhu; Jing Wang; Aijun Zhang; Zhonghou Tang (Plant, Soil and Environment, 2022)
This study aims to explore the effect of phosphorus (P) application on the economic yield, quality, P accumulation, and P utilisation efficiency of purple-fleshed sweetpotato and to provide a basis for the P efficient utilisation and high crop yield. Field experiments were conducted in 2018-2019, and five P application rates (0, 10.9, 21.8, 32.7, and 43.6 kg P/ha, expressed as P0, P1, P2, P3, and P4, respectively) were set. The results showed that P application significantly increased the yield and commodity potato yield of purple-fleshed sweetpotato, and that of P3 treatment was the highest, followed by P2 treatment. P application also increased the starch content in the storage root and increased the reducing sugar and soluble sugar (except for P2 treatment). P fertiliser supply significantly increased P accumulation and dry matter production of purple-fleshed sweetpotato during the growth period of 90 to 120 days. When the P application rate was over 21.8 kg/ha, the fertiliser investment rate, apparent P utilisation efficiency and P agronomic efficiency decreased with the increase of the application rate. Considering all the indexes, the supply of 21.8 kg/ha P fertiliser can meet the demand for high economic yield and P efficient utilisation in purple-fleshed type sweetpotato under the condition of this experiment.